Understanding Obsessive Compulsive Disorder and Management Options (Faridpur Medical College Journal, 2020)
Obsessive compulsive disorder is a common mental health problem. It is characterized by obsession and compulsion. Obsession can be defined as unwanted, intrusive, recurrent and persistent thoughts, images or impulses which are not voluntarily produced, but are experienced as events that invade a person's consciousness. Compulsion can be defined as repetitive and seemingly purposeful behavior that is performed according to certain rules or in a stereotyped fashion and is not an end in itself but is usually intended to prevent some event or situation. The obsessions or compulsions interfere significantly with the person's normal routine, occupational functioning, usual social activities, or relationships. Obsessive-compulsive disorder and several related disorders are now put together into separate chapter in Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5). Literature search was performed with the key words "Obsessive Compulsive Disorder", "Obsession", "Compulsion", "Treatment of Obsessive-Compulsive Disorder". Representative and leading researches from last 25 years were included in the study. Modern concepts of OCD began to evolve in the nineteenth century. Obsessions, in which insight was preserved, were gradually distinguished from delusions, in which it was not. The core features of OCD are remarkably similar from one country to the next, but its manifestations may differ for reasons of culture and experience. OCD is typically a chronic disorder with a waxing and waning course. In classical psychoanalytic theory, OCD was considered a regression from the Oedepal phase to the anal psycho-sexual phase of development. Functional brain imaging studies have produced a model for pathophysiology of OCD which involves hyperactivity in certain subcortical and cortical regions. The idea that abnormality in serotonergic neurotransmission underlies OCD arose from the observation that clomipramine, which inhibits serotonin and norepinephrine reuptake, relieved symptoms, whereas noradrenergic reuptake inhibitors did not. During the last 40 years there has been considerable progress in the pharmacological management of OCD. Behavioral therapy is also considered as an effective way of controlling OCD. Cognitive Behavioral Therapy (CBT) is a well-documented intervention for children, adolescents, and adults with OCD. Other biological approaches for obsessive-compulsive disorder include neurosurgery, deepbrain stimulation, electroconvulsive therapy, and repetitive transcranial magnetic stimulation. The neurosurgical techniques of cingulotomy and capsulotomy may provide clinical improvement among some patients with treatmentrefractory obsessive-compulsive disorder. Overall, stereotactic surgery should be viewed as a last option in treating refractory obsessive-compulsive disorder.Faridpur Med. Coll. J. Jan 2020;15(1): 38-42